An Analysis of the Consumer Behavior of Rumah Sehat Thibbun Nabawi: A Study in Pekanbaru City and Batam City - Martias, Dony; Muklis, Muklis; Adriyani, Annesa; Muslim, Muslim (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
This study aims to determine and analyze the influence of culture, reference group, and belief on consumer purchasing decisions in the treatment of Rumah Sehat Thibbun Nabawi. This is a survey research. The population in this study was Rumah Sehat consumers in Pekanbaru city and Batam city using an accidental sampling technique. The number of samples was 96 respondents. This means that from each consumer, 96 samples were taken from Pekanbaru city and 96 from Batam city. The data were collected by using a questionnaire. The results of this study indicated that the alternative therapies (Rumah Sehat) in Pekanbaru city with culture and beliefs influence the purchasing decisions of Rumah Sehat consumers while the reference group does not influence the purchasing decisions of Rumah Sehat consumers. The culture, reference group, and belief influence the purchasing decisions of Rumah Sehat consumers in Batam city. Overall, there is a significant comparison between Rumah Sehat in Pekanbaru City and the consumers of Rumah Sehat in Batam city toward the consumer purchasing decisions in doing therapies in Thibbun Nabawi.